2017
DOI: 10.1590/1678-4162-9282
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da eficiência de cal virgem na inativação de ovos de nematoides - Strongyloides sp.) parasitos de pacas - Cuniculus paca ) criadas em cativeiro

Abstract: Avaliação da eficiência de cal virgem na inativação de ovos de nematoides (Strongyloides sp.) parasitos de pacas (Cuniculus paca) criadas em cativeiro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…larvae development, suggesting that liming may have affected egg viability. Ribeiro et al (2017) investigated the effect of lime on Strongyloides spp. eggs and concluded that 10% quicklime (w/v) had a high ability to inactivate eggs in stalls of pacas ( Cuniculus paca ) raised in captivity, due the alkalinization of soil.…”
Section: Discussionmentioning
confidence: 99%
“…larvae development, suggesting that liming may have affected egg viability. Ribeiro et al (2017) investigated the effect of lime on Strongyloides spp. eggs and concluded that 10% quicklime (w/v) had a high ability to inactivate eggs in stalls of pacas ( Cuniculus paca ) raised in captivity, due the alkalinization of soil.…”
Section: Discussionmentioning
confidence: 99%